Is Rhodamine 123 an Appropriate Fluorescent Probe to Assess P-Glycoprotein Mediated Multidrug Resistance in Vinblastine-Resistant CHO Cells? - Jordi Pétriz; José Enrique O’Connor; Mercè Carmona; Joan García‐López (Analytical Cellular Pathology)
Cellular drug resistance, which involves several mechanisms such as P‐glycoprotein (P‐gp) overexpression, kinetic and metabolic quiescence, or the increase in the intracellular levels of glutathione, limits the effectiveness of cancer treatment. It has been reported that functional assessment of the cationic dye rhodamine 123 (Rho123) efflux reveals accurately the drug‐resistant phenotype. To study cellular drug resistance, we have obtained a CHO‐K1 derived cell line resistant to vinblastine by means of multistep selection. This cell line (CHOVBR) displays high reactivity with a monoclonal antibody (MAb) (C219) directed against an internal domain of P‐gp, and an active Rho123 efflux, as shown by parallel flow cytometric and fluorometric assays. However, under similar experimental conditions, the drug‐sensitive parental cell line CHO‐K1 (as well as the myeloblastic KG1 and KG1a cell lines), was also able to pump Rho123 out. These parental CHO‐K1 cells had a very low reactivity against the C219 Mab, as confirmed by Western blot analysis. Both vinblastine and verapamil inhibited Rho123 efflux in CHO‐K1 cells, but had no effect on CHOVBR cultures. Also, deprivation of vinblastine for one month did not affect Rho123 efflux in these cells. Our results suggest that the activity of P‐gp appears to be essential, but not sufficient to confer drug resistance, and that Rho123‐based functional assays of drug resistance should be evaluated for each cellular experimental model.